Monitoring Notifikasi Status Services Pada Os Linux Menggunakan Bot Telegram - Steffi Adam; Afrina; Agus Suryadi (Bulletin of Computer Science Research, 2022)
Currently server monitoring is still done manually, servers sometimes experience downtime and trouble, namely several services such as Apache, MySQL often down or crash themselves, network administrators cannot always monitor the network they manage as a result of the many other jobs that must be done. For this reason, this research created a script that can be used to monitor services on the server. This research was conducted by collecting data, observing and researching the library using telegram bots and bash scripts as supporting applications in monitoring service activities. This study aims to make it easier for administrators to handle servers. With this system, you can send notifications via telegram to network administrators when a service dies and this system can revive the dead service by restarting it